2016
DOI: 10.1111/ijd.13234
|View full text |Cite
|
Sign up to set email alerts
|

Lichen planus and dyslipidemia: a systematic review and meta‐analysis of observational studies

Abstract: Despite considerable heterogeneity, this study demonstrated that LP was significantly associated with an increased risk of dyslipidemia and higher triglyceride levels. For patients presenting with LP, physicians should be cognizant of this association and consider screening them for dyslipidemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
2
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 35 publications
2
41
2
2
Order By: Relevance
“…In our study we did not find a significant association with autoimmune diseases except for thyroid disease ( López-Jornet et al, 2014 ). A meta-analysis of patients with LP found that they are at an increased risk for hyperlipidemia ( Lai et al, 2016 ). Interestingly in our study, we found a lower risk of dyslipidemia compared with controls and further investigation is necessary to determine the true risk.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study we did not find a significant association with autoimmune diseases except for thyroid disease ( López-Jornet et al, 2014 ). A meta-analysis of patients with LP found that they are at an increased risk for hyperlipidemia ( Lai et al, 2016 ). Interestingly in our study, we found a lower risk of dyslipidemia compared with controls and further investigation is necessary to determine the true risk.…”
Section: Discussionmentioning
confidence: 99%
“…This pathophysiologic mechanism is thought to be similar to lichen planus (LP), which LPP is believed to be a follicular variant of ( Bolduc et al, 2016 ). Although there are known associations of LP with autoimmune disorders, hyperlipidemia, metabolic syndrome, hypothyroidism, anxiety, and depression, the relationship between LPP and other diseases has been largely unexplored ( Garcia-Pola et al, 2016 , Hirota et al, 2013 , Lai et al, 2016 , López-Jornet et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…A disrupted plasma lipid profile is observed in a number of inflammatory dermatoses, e.g. psoriasis [22] or lichen planus [23]. A relationship between disorders in lipid metabolism and androgenetic alopecia was confirmed in two metaanalyses.…”
Section: Nadciśnienie Tętniczementioning
confidence: 86%
“…dyslipideMiA Dyslipidemie należą do najważniejszych modyfikowalnych czynników ryzyka sercowo-naczyniowego. Zaburzony profil lipidów w osoczu obserwuje się w wielu dermatozach zapalnych, takich jak łuszczyca [22] i liszaj płaski [23]. Związek między zaburzeniami gospodarki lipidowej a łysieniem androgenowym potwierdzono w dwóch metaanalizach.…”
Section: Insulin Resistanceunclassified
“…This pathophysiologic mechanism is thought to be similar to lichen planus (LP), which LPP is believed to be a follicular variant of (Bolduc et al, 2016). Although there are known associations of LP with autoimmune disorders, hyperlipidemia, metabolic syndrome, hypothyroidism, anxiety, and depression, the relationship between LPP and other diseases has been largely unexplored (Garcia-Pola et al, 2016;Hirota et al, 2013;Lai et al, 2016;López-Jornet et al, 2014).…”
Section: Introductionmentioning
confidence: 99%